Economic valuation of cactus pear production in semi-arid regions of Chile - Louhaichi, Mounir; Hassan, Sawsan; Yigezu, Yigezu; Leiva, Sebastián; Mora Gonzalez, Marcos; Saenz, Carmen (2022)
Dataset about cactus pear production and economic evaluation in Chile. The dataset is part of a survey series, targeting farmer planting cactus across 5 countries: Tunisia, India, Jordan, Mexico and Chile.